2000
DOI: 10.1359/jbmr.2000.15.4.640
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Osteoclast Differentiation Signals by Stromal Elements of Giant Cell Tumors

Abstract: The mechanisms by which primary tumors of the bone cause bone destruction have not been elucidated. Unlike most other lytic bone tumors, osteoclastomas, otherwise known as giant cell tumors (GCT), contain osteoclast-like cells within the tumor stroma. A new member of the TNF-ligand superfamily member, osteoclast differentiation factor (ODF/OPGL/RANKL/TRANCE), was recently identified. ODF was shown to directly stimulate osteoclastogenesis, in the presence of M-CSF. In this study, the expression of ODF was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(81 citation statements)
references
References 31 publications
0
78
1
2
Order By: Relevance
“…28 Expression of osteoclastogenic factors by GCTB mononuclear cells is in keeping with the hypothesis that these cells express growth factors promoting osteoclast formation. 20,29 VEGF-A and RANKL expression by GCTB giant cells and M-CSF expression in enriched cultures of GCTB giant cells has been reported in previous studies. 30 Previous work has shown that M-CSF can inhibit or stimulate osteoclast resorption activity depending on the resorption model and species of osteoclast employed.…”
Section: Osteoclastogenesis By M-csf Substitutes Rm Taylor Et Almentioning
confidence: 52%
“…28 Expression of osteoclastogenic factors by GCTB mononuclear cells is in keeping with the hypothesis that these cells express growth factors promoting osteoclast formation. 20,29 VEGF-A and RANKL expression by GCTB giant cells and M-CSF expression in enriched cultures of GCTB giant cells has been reported in previous studies. 30 Previous work has shown that M-CSF can inhibit or stimulate osteoclast resorption activity depending on the resorption model and species of osteoclast employed.…”
Section: Osteoclastogenesis By M-csf Substitutes Rm Taylor Et Almentioning
confidence: 52%
“…GCTB contains 3 histologically different cell types: round to oval polygonal or elongated mononuclear stromal tumor cells, a minor component of reactive rounded mononuclear cells of monocyte lineage representing precursors of the giant cells, and evenly scattered giant cells. In many publications, the mononuclear stromal cells are reported to overexpress RANKL and are thought to be the true neoplastic components of GCTB (2,7,10,13). These transformed mononuclear stromal cells have been shown to express many characteristics of mesenchymal stem cells that have differentiated along the osteoblast lineage but not to a completely differentiated osteoblast phenotype, with minimal expression of such factors as osteocalcin and alkaline phosphatase (14-17, 26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, GCTB is composed of sheets of neoplastic ovoid mononuclear cells with high RANK ligand (RANKL) expression, RANK-positive mononuclear cells of myeloid linage, and a randomly distributed population of large RANKexpressing osteoclast-like giant cells (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Many researchers have shown that the giant cell of GCTB is osteoclastic in nature (4,6,10) and that the true neoplastic cells are ovoid cells displaying markers of mesenchymal stem cells that have partially differentiated along the osteoblast lineage (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…OPG, RANKL and/or RANK expression are dysregulated in a number of cancers in bone, including osteoclastoma [135] and PCa [136]. RANKL expression was identified in the epithelium and stroma of clinical PCa specimens [136] and increasing levels correlate with increased stage of disease [137] suggesting that it can serve as a prognostic factor [138] [142,143].…”
Section: Receptor Activator Of Nfkb Ligandmentioning
confidence: 99%